2003
DOI: 10.1590/s0034-89102003000300003
|View full text |Cite
|
Sign up to set email alerts
|

Paridade e influência do vento sobre a freqüência de Anopheles marajoara, São Paulo

Abstract: OBJETIVO: Avaliar a influência da velocidade do vento sobre o comportamento da população de Anopheles marajoara e sua paridade. MÉTODOS: As capturas foram feitas a cada dois meses, de janeiro de 1999 a fevereiro de 2000, no município de Ilha Comprida, no Estado de São Paulo, com utilização de aspirador manual movido à pilha. Utilizou-se o teste de Mann-Whitney para verificar a possível influência do vento sobre o comportamento dos mosquitos capturados. Para determinar a paridade, utilizou-se a técnica de Polov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
4
0
3
Order By: Relevance
“…Yet, such approaches do not always reflect the actual meteorological conditions, which may be associated with and/or exert an influence on the abundance and behavior of different arthropods. In the present study, a different approach was employed, in which the climate readings on each collection day (e.g., wind velocity) were used to assess the frequency and behavior of adults [4,60,61]. The mean values of these conditions were recorded at 7, 15, and 30 days before each collection date to evaluate factors that may influence sand flies during their immature phases and during adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, such approaches do not always reflect the actual meteorological conditions, which may be associated with and/or exert an influence on the abundance and behavior of different arthropods. In the present study, a different approach was employed, in which the climate readings on each collection day (e.g., wind velocity) were used to assess the frequency and behavior of adults [4,60,61]. The mean values of these conditions were recorded at 7, 15, and 30 days before each collection date to evaluate factors that may influence sand flies during their immature phases and during adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Por isso, neste trabalhou foi adotada uma abordagem diferente, que considera as aferições climáticas no dia de cada coleta, como uma alternativa de verificar condições que pudessem afetar a frequência e comportamento dos adultos durante a coleta, como o a velocidade do vento, conforme relatado por outros autores (GARMS et al, 1979;KAKITANI et al, 2003;OLIVEIRA et al, 2013a .…”
Section: Discussionunclassified
“…By analyzing the influence of wind on the biting activity and population frequency of Anopheles marajoara (Diptera: Culicidae), Kakitani et al found highly significant values, and on wind speed less than 3.0 km/h, the frequency of mosquitoes decreased considerably. Besides the negative association with wind speed, Ximenes et al reported a positive association with temperature for the total females, with relative humidity for a total of males and females, and with total rainfall for females of L. longipalpis in the forest region of northeast Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…The standard of transmission and distribution of a disease vector can be modified by environmental factors and the easy adaptation of the vector associated with migration, as observed in the sand fly Lutzomyia longipalpis (Bejarano et al ). In recent years, there have been several studies that correlated health to the environment by assessing the impact exerted by abiotic factors on the occurrence and abundance of arthropod vectors of diseases (Kakitani et al , Vazquez‐Prokopec et al ).…”
Section: Introductionmentioning
confidence: 99%